THE IMPACT OF DIFFERENT REGIMENS OF VITAMIN D3 ON GLUCOSE HOMEOSTASIS IN TYPE 2 DIABETIC PATIENTS - SAMIA MOHAMED ALI; YEHIA MOSTAFA GHANEM; OLA ATEF SHARAKI; WAFAA AHMED HEWEDY; ESRAA SAEED HABIBA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Vitamin D has a role in the regulation of pancreatic β-cell function and insulin sensitivity. Accordingly, Vitamin D deficiency is considered to be a risk factor for the development of type 2 diabetes mellitus (T2DM) and its complications. Therefore, the aim of the study was to assess and compare the effect of different regimens of Vitamin D3 on glucose homeostasis in patients with T2DM. Methods: The study included 80 patients with T2DM taking oral antidiabetic drugs. The patients were randomized to receive antidiabetic drugs alone or with different regimens of Vitamin D3 for 3 months. Vitamin D3-treated patients were supplemented by either daily oral 4000 IU Vitamin D3, weekly oral 50,000 IU Vitamin D3, or a single parenteral dose of 300,000 IU Vitamin D3. In addition to the assessment of patient characteristics, laboratory measurements of serum creatinine, blood urea, total and ionized calcium, serum phosphorus, fasting blood glucose, fasting serum insulin, homeostasis model assessment of insulin resistance, hemoglobin A1c, and 25(OH) Vitamin D levels were measured at the beginning and after 3 months. Results: After 3 months, the increased Vitamin D levels resulting from the daily and weekly oral doses of Vitamin D3 caused a significant decrease in metabolic parameters, whereas the parenteral dose demonstrated a non-significant decrease. Conclusion: Oral daily and weekly doses of Vitamin D3 could improve glucose homeostasis equally in patients with T2DM and better than a single parenteral dose of Vitamin D3.